Penerapan Pembelajaran Berdiferensiasi dalam Peningkatan Hasil Belajar IPAS Kelas 5 SDN Sawah Besar 01 Semarang - Anisatur Rohmaniyah; Mei Fita Asri Untari; Nani Kurniasari (Journal on Education, 2024)
This research aims to determine whether student learning outcomes are better after implementing differentiated learning in science subjects in the VA class of SDN Sawah Besar 01 Semarang, which consists of 28 students, consisting of 13 male students and 15 female students. Tests on student learning outcomes, interviews and observations are the data collection methods used. Differentiated learning is applied to VA class students at SDN Sawah Besar 01 Semarang. This is done to increase students' interest and learning outcomes because learning has been implemented that suits students' interests and learning styles. Classroom Action Research (CAR), designed by Kemmis and M.C. Taggart, uses four stages: planning, implementing, observing, and reflecting. The research results show an increase in the implementation of differentiated learning in science and science subjects in the VA class of SDN Sawah Besar 01 Semarang in the first semester of the 2023/2024 academic year. Student learning outcomes show an increase in percentage and average. This was seen in the pre-cycle, with a percentage of 18% with an average value of 68.75, in cycle I, with a percentage of 46% with an average value of 72.86, and in cycle II, with a percentage of 82% with an average value of class average 80. Therefore, differentiated learning in science and science subjects in the VA class of SDN Sawah Besar 01 Semarang is considered successful and can be applied during the learning process.